1975
DOI: 10.1115/1.3423596
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of Restitution Interpreted as Damping in Vibroimpact

Abstract: During impact the relative motion of two bodies is often taken to be simply represented as half of a damped sine wave, according to the Kelvin-Voigt model. This is shown to be logically untenable, for it indicates that the bodies must exert tension on one another just before separating. Furthermore, it denotes that the damping energy loss is proportional to the square of the impacting velocity, instead of to its cube, as can be deduced from Goldsmith’s work. A damping term λxnx˙ is here introduced; for a spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
781
0
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,356 publications
(798 citation statements)
references
References 4 publications
4
781
0
13
Order By: Relevance
“…Hunt and Crossley [31] showed that the linear spring-damper model does not represent the physical nature of energy transferred during the contact. Instead, they represented the contact force by the Hertz force-deformation law with a nonlinear viscous-elastic element as…”
Section: General Issues Of Continuous Contact Force Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hunt and Crossley [31] showed that the linear spring-damper model does not represent the physical nature of energy transferred during the contact. Instead, they represented the contact force by the Hertz force-deformation law with a nonlinear viscous-elastic element as…”
Section: General Issues Of Continuous Contact Force Modelsmentioning
confidence: 99%
“…Based on the analysis of Hunt and Crossley [31] that separates the contact force into elastic and dissipative components, the force model proposed by Lankarani and Nikravesh can be expressed as…”
Section: General Issues Of Continuous Contact Force Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To search the wheel contact, a kinematic formulation of the track layout is utilized assuming the track to be rigid and all track sections to by perfectly aligned and tangent to each other. The wheel and joint contacts are modeled using the continuous Hunt-Crossly formulation in which the contact force are computed by the indentation and the indentation velocity between the intersecting bodies, see Hunt and Crossley (1975). The motor force is applied as a point force onto the bottom of all carts located above a linear motor.…”
Section: Model Of Chain Dynamicsmentioning
confidence: 99%
“…A significant number of such force models is available (e.g. [10], [12], [7], [19]). These are often based on the assumption of Hertzian contact together with various representations for dissipation.…”
mentioning
confidence: 99%